Distant Corners : American Soccer's History of Missed Opportunities and Lost Causes - Wangerin, David (Book collections on Project MUSE., 2011)
In Distant Corners, his follow-up to Soccer in a Football World, David Wangerin details several of the people, places, and events that shaped American soccer history. Despite its struggle for popular acceptance, soccer in the United States has a rich history. Wangerin profiles Tom Cahill, the almost-forgotten ""father of American soccer, "" and writes passionately about the 1979 North American Soccer League season, the high-water mark of the game in the twentieth century. Wangerin shows how the American appetite for soccer has ebbed and grown over the years, chronic.